Tax Compliance as a Social Responsibility Practice: An Interpretive Study from a Social Accounting Perspective - Muarif Leo; Alimuddin; Syarifuddin (LP2M IAIN Palopo, 2026)
Tax compliance has traditionally been understood primarily as a legal and administrative obligation that emphasizes regulations, penalties, audits, and reporting procedures; as a result, existing frameworks remain limited in explaining how taxpayers perceive compliance as part of their social responsibility. This study aims to interpret the meaning of tax compliance as a practice of social responsibility from a social accounting perspective. The study employs an interpretive qualitative approach, with data collected through semi-structured interviews with four individual taxpayers as the primary informants. The data were analyzed through the stages of open coding, categorization, theme formation, interpretation of meaning, and conceptual synthesis. The research findings reveal five main themes: taxes as a social contribution; tax compliance as a form of concern for society; tax compliance as a moral obligation of citizens; taxation as a form of fiscal solidarity; and the importance of education, transparency, and institutional legitimacy in fostering compliance. These findings indicate that tax compliance is not merely interpreted as adherence to rules, but as a social practice built upon moral responsibility, collective solidarity, public trust, and accountability. This study contributes to the development of social accounting literature by introducing the concept of fiscal solidarity as a collective practice of citizens in supporting public welfare and strengthening the relationship between society, the state, and the tax system.